Evaluation of Peripheral Blood Eosinophilia in Adolescent and Adult Patients Suffering from Atopic Dermatitis and the Relation to the Occurrence of Allergy to Aeroallergens - Celakovská, Jarmila; Bukac, Josef; Ettler, Karel; Vaneckova, Jaroslava; Krcmova, Irena; Ettlerova, Kvetuse; Krejsek, Jan (Indian journal of dermatology, 2019)
Background: Eosinophils play an important pathogenic role in atopic dermatitis (AD), but its exact function remains to be determined. Aims and Objectives: The aim of this study was to correlate the eosinophil count with the manifestations such as asthma bronchiale, rhinitis, level of total IgE, sensitization to mites, animal dander, bird feather, dust, mixture of grass, mixture of trees, mixture of fungi, duration of lesions (persistent or occasional during last year), family history about atopy, and onset of AD (under or above 5 year of age). Materials and Methods: Two hundred and seventy-two patients suffering from AD at the age of 14 year or older were examined - 100 men and 172 women with the average age of 26.7±9.5 years and with the average SCORAD index of 32.9±14.1. Complete dermatological and allergological examinations were performed in all patients with the evaluation of monitored manifestations. Mann-Whitney test for difference in medians was used for statistical evaluation. Results: The count of eosinophils in peripheral blood was significantly higher in patients with total IgE ≥200 IU/ml, with sensitization to dust, with persistent eczematous lesions and in patients with the onset of AD under 5 year of age. The count of eosinophils above 5% was recorded as well in patients suffering from asthma bronchiale, rhinitis, sensitization to mites, and in patients with positive family history about atopy, but the difference was not significant. On the other hand, the count of eosinophils was under 5% in patients with sensitization to animal dander, bird feather, mixture of grass and trees. Conclusion: Our results demonstrated the difference in the count of eosinophils in peripheral blood according to different manifestations in patients suffering from AD.